TEACHING ENGLISH TO STUDENTS OF DENA UPAKARA WONOSOSOBO - Christina Christina (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
Learning English as a foreign language is one of the mandatory subjects for junior high schools students in Indonesia. This subject is also among the subjects tested in national examination. This means that English is being taught in every high school, be it schools for normal students or schools for disabled students. Teaching English to students with hearing impairment is a challenge. This study aims to describe how English is taught for students in Dena Upakara School for the deaf in Wonosobo. It means the researcher explores what teaching methods are employed in the learning-teaching process. An observation and interviews were conducted to gather information on the question. The students involved in this study are students of the 7th grade. The result reveals that the teacher combines several methods to deliver the material. The methods employed by the teacher include the grammar-translation method, natural method, and lexical approach.